2021
DOI: 10.1167/iovs.62.3.30
|View full text |Cite
|
Sign up to set email alerts
|

Extensive Sub-RPE Complement Deposition in a Nonhuman Primate Model of Early-Stage Diabetic Retinopathy

Abstract: Purpose This study aims to reveal retinal abnormities in a spontaneous diabetic nonhuman primate model and explore the mechanism of featured injuries. Methods Twenty-eight cynomolgus monkeys were identified to suffer from spontaneous type 2 diabetes from a colony of more than eight-hundred aged monkeys, and twenty-six age-matched ones were chosen as controls. Their blood biochemistry profiles were determined and retinal changes were examined by multimodal imaging, hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Evidences from animal model showed that blocking the TNF-α significantly reduced the vascular change induced by diabetes, such as loss of pericyte ( Behl et al, 2008 ; Semeraro et al, 2015 ). Our previous work observed the microangiopathy with remarkable acellular capillaries and pericyte loss in monkeys with spontaneous DM ( Fan et al, 2021 ). TNF-α increase retinal endothelial permeability by increased the expression of ANG2 and downregulated the expression of tight junction proteins ( Kim et al, 2000 ; Fiedler and Augustin, 2006 ; Aveleira et al, 2010 ).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Evidences from animal model showed that blocking the TNF-α significantly reduced the vascular change induced by diabetes, such as loss of pericyte ( Behl et al, 2008 ; Semeraro et al, 2015 ). Our previous work observed the microangiopathy with remarkable acellular capillaries and pericyte loss in monkeys with spontaneous DM ( Fan et al, 2021 ). TNF-α increase retinal endothelial permeability by increased the expression of ANG2 and downregulated the expression of tight junction proteins ( Kim et al, 2000 ; Fiedler and Augustin, 2006 ; Aveleira et al, 2010 ).…”
Section: Discussionmentioning
confidence: 95%
“…As described previously, Cynomolgus monkeys with spontaneous type 2 diabetes were screened in southern china, and diagnosed as diabetes with the parameters of fasting glucose and HbA1c levels as described before. Non-diabetic age-matched controls were selected randomly from the colony ( Fan et al, 2021 ). All animals were maintained at 25°C on a 12 h light:12 h dark schedule.…”
Section: Methodsmentioning
confidence: 99%
“… 50 Fan et al observed not only typical vascular and neural damage but also sub-RPE drusenoid lesions in a non-human primate model of early-stage diabetic retinopathy. 51 However, they also found that the RPE drusenoid lesion required complement activation to establish an environment of chronic inflammation circumstance, and the inflammation involvement and immune cell recruitment may play an important role in this mechanism. Therefore, we hypothesise that the anti-inflammatory effect of metformin might be more significant in the protection against RPE drusenoid lesion, than against diabetic vascular damage.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are scarce data on changes in gene expression induced by excessive GV, there is a large pool of studies on gene profiling related to hyperglycemia. Using high-throughput technologies, differential gene expression was measured under hyperglycemic conditions in beta cells [140,141], pancreatic cells [142], hepatic cells [143,144], endothelial cells [145], myotubes [146], cardiomyocytes [147], vascular smooth muscle cells [148,149], adipose progenitor cells [150], kidney cells [151], renal tubular epithelial cells [152], retina [153,154], immune cells [155,156] and others. The genes that demonstrate an altered expression in hyperglycemia are mostly involved in glucose metabolism, inflammation and immune processes, endothelial dysfunction, angiogenesis, oxidative stress, mitochondrial dysfunction, hypoxia and cell death.…”
Section: Gene Expressionmentioning
confidence: 99%